2011
DOI: 10.4103/0250-474x.100235
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fluoxetine on an experimental model of diabetes-induced neuropathic pain perception in the rat

Abstract: The aim of the present study was to study the effect of chronic treatment (9 weeks) of fluoxetine (20 mg/kg p.o.) a selective serotonin reuptake inhibitor on blood glucose level and in prevention of diabetic neuropathic pain perception. Evaluation of diabetic neuropathy was performed after 9 weeks of single injection of streptozotocin (70 mg/kg i.v.) in rats. Blood glucose level, glycated haemoglobin, grip strength, pain sensitivity and threshold in diabetic rats were measured at the end of 9 weeks. The result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 17 publications
2
7
0
Order By: Relevance
“…In accordance with this finding, Tembhurne and Sakarkar (2011) have revealed that a 9 week treatment with Flu (20.0 mg·kg −1 , per oral) decreased the glycaemic index and protected STZ-induced diabetic rats from diabetic neuropathy. Moreover, clinical studies have reported the effectiveness of Flu in reducing the severity of depression as well as hyperglycaemia in diabetic patients, leading to better glycaemic control (Goodnick 2001;Khazaie et al 2011).…”
Section: Notesupporting
confidence: 81%
“…In accordance with this finding, Tembhurne and Sakarkar (2011) have revealed that a 9 week treatment with Flu (20.0 mg·kg −1 , per oral) decreased the glycaemic index and protected STZ-induced diabetic rats from diabetic neuropathy. Moreover, clinical studies have reported the effectiveness of Flu in reducing the severity of depression as well as hyperglycaemia in diabetic patients, leading to better glycaemic control (Goodnick 2001;Khazaie et al 2011).…”
Section: Notesupporting
confidence: 81%
“…Park et al (33), revealed that 90% pancreatic resection increased glucose clearance and decreased blood insulin levels following 8 weeks of fluoxetine treatment. Tembhurne et al (34) reported that fluoxetine reduced the levels of FBG and improved glucose tolerance in rats with STZ-induced diabetes. In summary, fluoxetine may reduce blood glucose and body weight loss, and improve insulin resistance; however, the underlying molecular mechanisms remain unknown.…”
Section: Discussionmentioning
confidence: 99%
“…It has been observed that there is loss of pain perception, and it is thought to be due to nerve damage and induction of peripheral neuropathy. 18 …”
Section: Discussionmentioning
confidence: 99%